2015
DOI: 10.2214/ajr.14.13454
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated CT-Based Quantification of Donor Kidney Volume Applied to a Predictive Model of Outcomes in Renal Transplantation

Abstract: The CT-derived ratio between donated kidney cortical volume and recipient pretransplant weight is a noninvasively and readily obtained reproducible biomarker that is predictive of 12- and 24-month renal transplant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Longer term renal function would be useful as an outcome; however, given the relatively new requirement to collect postdonation renal function, our study is limited to the 2-year postdonation mark. In addition, one reader assessed kidney volumes; however, previous studies that investigated intraand interobserver variability did not find major interobserver discrepancies with the CT volumetric method used for this study (15,26). In addition, multiple CT scanners with variable protocols and section thicknesses were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer term renal function would be useful as an outcome; however, given the relatively new requirement to collect postdonation renal function, our study is limited to the 2-year postdonation mark. In addition, one reader assessed kidney volumes; however, previous studies that investigated intraand interobserver variability did not find major interobserver discrepancies with the CT volumetric method used for this study (15,26). In addition, multiple CT scanners with variable protocols and section thicknesses were used.…”
Section: Discussionmentioning
confidence: 99%
“…A board-certified radiologist (G.F., with 4 years of post-abdominal imaging fellowship experience) used commercially available semiautomatic volumetric analysis to retrospectively measure image volumes (IntelliSpace Portal, V7.02.60020; Philips Healthcare, High- land Heights, Ohio). The nephrographic phase images were used to measure whole kidney volume, and the arterial phase images were used to measure cortical volume of the remnant kidney (15). With use of the axial, sagittal, and coronal images, a pointer was placed over the remnant kidney (either the cortex and medulla to provide whole kidney volume or just the cortex to provide cortical volume) with a growing region of interest (Fig 1a and 1b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there remains an issue of difficulty to interpret the number of nephrons in an individual based solely on knowledge of cortical volume. In fact, previous reports of cortical volume did not consistently find correlations with either nephron number or renal outcomes 19,20 .…”
Section: Discussionmentioning
confidence: 58%
“…A recent study evaluated renal cortical volume using computed tomography (CT) to predict graft function in living donor kidney transplants, although that was not necessarily correlated with graft survival [7,8]. Another study showed that US measurements, especially cortical thickness, were good for evaluating renal function [9].…”
Section: Discussionmentioning
confidence: 99%